Exponentials of general multivector in 3D Clifford algebras - Dargys, Adolfas; Acus, Artūras (Nonlinear Analysis: Modelling and Control, 2022)
Closed form expressions to calculate the exponential of a general multivector (MV) in Clifford geometric algebras (GAs) Clp;q are presented for n = p + q = 3. The obtained exponential formulas were applied to find exact GA trigonometric and hyperbolic functions of MV argument. We have verified that the presented exact formulas are in accord with series expansion of MV hyperbolic and trigonometric functions. The exponentials may be applied to solve GA differential equations, in signal and image processing, automatic control and robotics.
Keywords: Clifford (geometric) algebra; exponentials of Clifford numbers; computer-aided theory